Human Capital of Family and Social Mobility in Rural Areas – Evidence from China - Jin-hua ZHANG; Mei-lian YU; Fang-wei WU; Wei CHEN (Journal of Integrative Agriculture, 2013)
This research focuses on the impact of family's human capital on social mobility in China's rural community. Empirical research is conducted based on data from surveying a typical rural community in the past 20 yr. The study indicates that social mobility in rural area is active in the past 20 yr, and the human capital of family, represented by primary labor's education level, has played an essential role in mobility of low social class. Meanwhile, socio-economic development and the change of supply and demand in labor market dims the signaling role of degree education, but the impact of occupational training is increasingly remarkable. Therefore, the change from sole degree education to multi-leveled education including occupational education and training is a main way for China's rural families in low class to realize social mobility.